BRAND DEVELOPMENT THROUGH COMMUNITY IDENTITY AND INTEGRATED MARKETING COMMUNICATIONS THROUGH COMMUNITY PARTICIPATION - Suwannee, Sittisak; Sansomedang, Patsinee; Thularate, Nanthara; Roemsri , Jiraphat; Sripasuda, Ladapa (Journal of Graduate School Sakon Nakhon Rajabhat University, 2025)
This research has the objective to develop brands through community identity through community participation. and integrated marketing communications. This research uses participatory action research (PAR) using a mixed method, consisting of qualitative research and quantitative research. Data were collected through in–depth interviews, focus group discussions, data collection in the form of documents, textbooks, articles, research, and integrated community product marketing communication questionnaires. The case study was the Pla Ra Bong Phithak Tham Community Enterprise Group, Ban Dong Mafai, Khammin Subdistrict, Mueang District, Sakon Nakhon Province. The research findings revealed that in designing brands through community identity, designers should be involved in understanding and absorbing the community’s identity and way of life until they become one with the community. This leads to the development of brands and packaging that meet the needs and have interesting and memorable forms. It can communicate the benefits of the product, making consumers feel the quality they receive. It has a clear personality, looks modern, and does not fall out of date. Good brand development design should be approved by the members of the community who own the product and reflect the existing identity of the community. Until being able to develop a brand under the name "Pla Ra Bong Phithaktham". After the product and brand design process, the researchers reviewed the literature to study the channels for integrated product marketing communication through five channels: 1) advertising, 2) public relations, 3) sales promotion, 4) sales force, and 5) direct marketing. After conducting integrated marketing communication, it was found that the use of integrated communication through these channels can effectively create and promote product sales. It is convenient, reduces communication costs, and collects consumer data for future sales promotion. However, communication must be continuous, diverse, and cover both online and offline media. It must also communicate in the same direction in order to build on and create a stable career in the future.